2020
DOI: 10.3389/fbioe.2020.599674
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Therapy Manufacturing in Stirred Suspension Bioreactor: Thoughts for cGMP Compliance

Abstract: Cell-based therapy (CBT) is attracting much attention to treat incurable diseases. In recent years, several clinical trials have been conducted using human pluripotent stem cells (hPSCs), and other potential therapeutic cells. Various private- and government-funded organizations are investing in finding permanent cures for diseases that are difficult or expensive to treat over a lifespan, such as age-related macular degeneration, Parkinson’s disease, or diabetes, etc. Clinical-grade cell manufacturing requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 179 publications
1
21
0
Order By: Relevance
“…Researchers have reported that 3D bioreactors differentiate DPSCs into different cell types, including neural progenitor cells and adipose-like structures. 32 , 33 , 34 In our results, 2D and 3D cultures treated with THSG induced neurogenic ( Fig. 6 ) and adipogenic ( Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Researchers have reported that 3D bioreactors differentiate DPSCs into different cell types, including neural progenitor cells and adipose-like structures. 32 , 33 , 34 In our results, 2D and 3D cultures treated with THSG induced neurogenic ( Fig. 6 ) and adipogenic ( Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, several studies have reported the osteogenic, adipogenic, and pluripotent differentiation of MSCs in 3D bioreactors. 32 Although 3D culture improved the differentiation and dedifferentiation in MSCs, prolonged in vitro expansion causes various types of damage, such as rapid aging and stemless loss. 28 Our previous studies have demonstrated that THSG improves self-renewal and osteogenic differentiation in DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, biomanufacturing technologies based on 3D-bioreactors for large and ultra-large scale-up of cell production are beneficial. [115,116] In addition, processes for large-scale cell membrane derivation, efficient nanoparticle coating, and reliable quality control methods are also required. Overall, with continuous research and development, we expect the cellular nanosponge technology will reveal and demonstrate more unique strengths towards biological neutralization applications, which will benefit various patient populations.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Methods and tools (such as bioreactors) that work well at bench‐scale may be difficult to reproduce at scale particularly if they are prone to contamination or yielding variable culture batches. 13 Thus, it is important to allow sufficient development time to demonstrate proficiency and reliability of the proposed scale‐up mechanism.…”
Section: The Challenges Of Manufacture Of Cellular Products As Compar...mentioning
confidence: 99%